2007
DOI: 10.1021/nl070610y
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Resonant Nanoshells for Combined Optical Imaging and Photothermal Cancer Therapy

Abstract: Metal nanoshells are core/shell nanoparticles that can be designed to either strongly absorb or scatter within the near-infrared (NIR) wavelength region ( approximately 650-950 nm). Nanoshells were designed that possess both absorption and scattering properties in the NIR to provide optical contrast for improved diagnostic imaging and, at higher light intensity, rapid heating for photothermal therapy. Using these in a mouse model, we have demonstrated dramatic contrast enhancement for optical coherence tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
1,031
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,244 publications
(1,049 citation statements)
references
References 29 publications
5
1,031
1
6
Order By: Relevance
“…Using nanoshells with a 110 nm silica core diameter and a 10 nm Au shell, the authors reported significant reduction of human breast carcinoma epithelial cells (SK-Br-3) both in vitro and in a mouse model. Since then there have been many accounts of laser initiated hyperthermia using a variety of nanoparticles with solid Au spheres, cubes, stars, shells and rods all demonstrating successful results in photothermal applications [119,167,189,197,[206][207][208][209][210][211][212].…”
Section: Photothermal Ablation (Pta) Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Using nanoshells with a 110 nm silica core diameter and a 10 nm Au shell, the authors reported significant reduction of human breast carcinoma epithelial cells (SK-Br-3) both in vitro and in a mouse model. Since then there have been many accounts of laser initiated hyperthermia using a variety of nanoparticles with solid Au spheres, cubes, stars, shells and rods all demonstrating successful results in photothermal applications [119,167,189,197,[206][207][208][209][210][211][212].…”
Section: Photothermal Ablation (Pta) Therapymentioning
confidence: 99%
“…While PTA has proven to be an effective method of eradicating cancer cells both in vitro and in vivo, its application remains limited by the fact that the diffusion of heat through tissue at increasing depths of penetration is not uniform [198,208,224]. This means that some portions of the tumor cells will reach an appropriate temperature to induce apoptosis and some will not.…”
Section: Multi-modal Treatmentsmentioning
confidence: 99%
“…The use of plasmonic nanomaterials in photothermal therapy of tumors has received increasing attention over the past few years, [1][2][3][4][5][6][7][8][9] primarily because of the directivity, specificity, and nonintrusive nature of the underlying treatment protocol. Tumor-targeted nanoantennas are ideally suited for many of these applications.…”
mentioning
confidence: 99%
“…These nanoantennas exploit the geometrically tunable surface plasmon resonance ͑SPR͒ phenomenon of metal nanoparticles, whereby external electromagnetic fields can induce the resonant oscillation of nanoparticle free electrons and allow efficient photothermal conversion of the nonradiative extinction component to heat through electron-electron and electron-phonon relaxation mechanisms. [2][3][4][5][6][7][8][9] Further, surface-modification of nanostructured plasmonic materials with polymers and targeting ligands has enabled those to evade rapid clearance from the blood stream and intravenously target tumors via unique biological tumor characteristics, thereby enabling highly specific heating of tumor cells under laser irradiation with wavelengths overlapping the nanoparticle SPR absorption regime. [2][3][4][5][6][7][8][9] While preclinical tests with tumor-targeted nanoantennas have produced impressive results, 10 few efforts have been made to quantitatively model and predict four-dimensional temperature gradients 11 in tumors and neighboring tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation